2017
DOI: 10.1158/1538-7445.am2017-1796
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 1796: A targeted RNA-seq assay to measure activating ER mutations and ER/PR-associated gene expression predicts sensitivity to endocrine therapy for metastatic breast cancer

Abstract: Background: We developed SET4 as a targeted, droplet-based, next-generation RNA sequencing assay to measure both the SETER/PR index of gene expression and the percent of estrogen receptor (ER) transcripts with point mutation in the ligand-binding domain (LBD) in metastatic biopsies of Stage IV breast cancer. The SETER/PR index (31 genes) is a cumulative measure of gene expression for transcripts associated with ER and progesterone receptor (PR), excluding those with a direct role in proliferation. High SETER/P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The median age of patients in the included studies ranged between 44–68 years; age was not reported in 12 studies. 28 , 31 , 55 , 66 , 84–87 , 93 , 97 In 22 studies, the entire study population was HR+ and HER2–, while in eight studies the proportion of patients with HR+ and/or HER2– status was between 80–99%, and the remaining 49 studies included patients with HR+ and/or HER2– status ranging between 50–79%.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The median age of patients in the included studies ranged between 44–68 years; age was not reported in 12 studies. 28 , 31 , 55 , 66 , 84–87 , 93 , 97 In 22 studies, the entire study population was HR+ and HER2–, while in eight studies the proportion of patients with HR+ and/or HER2– status was between 80–99%, and the remaining 49 studies included patients with HR+ and/or HER2– status ranging between 50–79%.…”
Section: Resultsmentioning
confidence: 99%
“…However, these were reported sparsely and we could not assess strength of evidence for them. They consisted of many genetic/biomarkers factors, for example, estrogen receptor gene (ESR1) mutation status, 68 ligand binding domain (LBD) status, 97 CA 15–3 level, 51 , 70 alkaline phosphatase level, 79 serum C-reactive protein level (CRP), 79 lactic acid dehydrogenase (LDH) level, 51 , 59 , 79 along with other demographic-related factors like marital status, 55 income level, 55 menopausal status, 59 and education status. 55 A high level summary can be found in Table 3 .…”
Section: Resultsmentioning
confidence: 99%